Dispersals and Diversification : Linguistic and Archaeological Perspectives on the Early Stages of Indo-European. - Serangeli, Matilde (Brill's Studies in Indo-European Languages and Linguistics Ser., 2020)
"Dispersals and diversification offers linguistic and archaeological perspectives on the disintegration of Proto-Indo-European, the ancestor of the Indo-European language family. Two chapters discuss the early phases of the disintegration of Proto-Indo-European from an archaeological perspective, integrating and interpreting the new evidence from ancient DNA. Six chapters analyse the intricate relationship between the Anatolian branch of Indo-European, probably the first one to separate, and the remaining branches. Three chapters are concerned with the most important unsolved problems of Indo-European subgrouping, namely the status of the postulated Italo-Celtic and Graeco-Armenian subgroups. Two chapters discuss methodological problems with linguistic subgrouping and with the attempt to correlate linguistics and archaeology. Contributors are David W. Anthony, Rasmus Bjørn, José L. García Ramón, Riccardo Ginevra, Adam Hyllested, James A. Johnson, Kristian Kristiansen, H. Craig Melchert, Matthew Scarborough, Peter Schrijver, Matilde Serangeli, Zsolt Simon, Rasmus Thorsø, Michael Weiss."